Rattus norvegicus - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus norvegicus (Berkenhout 1769) [Mus] norvegicus Berkenhout 1769, Outlines of the Natural History of Great Britain and Ireland, Vol. 1: 5. Type Locality: Great Britain. Vernacular Names: Brown Rat. Synonyms: Rattus aquaticus (Rutty 1772); Rattus albinus (Donaldson 1912); Rattus albus Hatai 1907; Rattus americanus (de Kay 1842); Rattus caraco (Pallas 1778); Rattus caspius (Oken 1816); Rattus cauquenensis (Philippi 1900); Rattus decaryi (Grandidier 1934); Rattus decumanoides (Hodgson 1841); Rattus decumanus (Pallas 1779); Rattus discolor (Noack 1918); Rattus fossilis (Ameghino 1889); Rattus fossor (Walker 1808); Rattus griseipectus (Milne-Edwards 1872); Rattus hibernicus (Thompson 1837); Rattus hoffmanni (Trouessart 1904); Rattus humiliatus (Milne-Edwards 1868); Rattus hybridus (Bechstein 1800); Rattus insolatus Howell 1927; Rattus javanus (Hermann 1804); Rattus kurodobu Kuroda 1953; Rattus leucosternum (Rüppell 1842); Rattus lutescens (Gay 1848); Rattus magnirostris (Mearns 1905); Rattus major (Hoffmann 1887); Rattus maniculatus (Wagner 1848); Rattus maurus (Waterhouse 1839); Rattus migrans (Zimmermann 1777); Rattus orii Kuroda 1952; Rattus otomoi Yamada 1930; Rattus ouangthomae (Milne-Edwards 1871); Rattus plumbeus (Milne-Edwards 1874); Rattus praestans (Trouessart 1904); Rattus primarius Kastschenko 1912; Rattus shirokuma Kuroda 1953; Rattus simpsoni (Philippi 1900); Rattus socer Miller 1914; Rattus sowerbyi Howell 1928; Rattus suffureoventris Kuroda 1952; Rattus surmulottus (Severinus 1779); Rattus tamarensis (Higgins and Petterd 1883). Distribution: Original distribution assumed to be SE Siberia, N China (Heilongjiang), and Hondo region (islands of Honshu, Shikoku, and Kyushu; see Dobson, 1994) of Japan (Jones and Johnson, 1965; Kowalski and Hasegawa, 1976; Kawamura, 1989), but introduced worldwide where it is more common in colder climates of higher N and S latitudes (Kucheruk, 1990); in warmer regions and tropics restricted to habitats highly modified by humans (e. g., sewers, buildings, wharves, ...